(untitled) (Agroindustrial Science, 2026)
This study investigates the spatial distribution of *Trichogramma* spp. in the Lambayeque region of Peru, assessing its potential as a biological control agent against lepidopteran pests in agroecosystems.** Data were collected between January and June 2024 in key districts such as Lambayeque, Ferreñafe, and Chiclayo, using sentinel traps baited with Sitotroga cerealella eggs. The results reveal high parasitism efficacy (>75%) in areas such as Lambayeque, Motupe, and Salas, while locations like Cayaltí and Chilcal recorded no parasitic activity. The observed distribution suggests the influence of factors such as egg density and microclimatic conditions. However, the analysis was limited by a small sample size (14 valid records), which affected the statistical power for comparing host species and locations. Kruskal-Wallis tests found no significant differences (p > 0.05), and regression models explained only 59.7% of the variance, constrained by the lack of environmental data such as temperature and crop type. The Kriging geospatial tool was used to map distribution, revealing heterogeneous patterns that provide a crucial foundation for future research. The study concludes that Trichogramma spp. has potential for pest control in specific areas of Lambayeque but recommends expanding sampling efforts, including climatic variables, and conducting molecular identification of species. Future research should explore integrated approaches with entomopathogenic fungi to optimize targeted release strategies and promote sustainable agriculture in the region.